Worked Example X Aula Expositiva no aprendizado de Radiologia de estudantes de Medicina - Paola Isabel Silva Barros (2019)
Context: Much has been discussed about the use of lectures during medical education despite the extensive incorporation of teaching models not based on this technique. The Worked Example is an instructional tool in which an expert shows a detailed problem solution for a learner. We compared, in an experimental study with medical students, lectures x Worked Example for teaching chest tomography. Methods: Participants were allocated into two large groups according to the phase of medical school they were attending and were randomly assigned to two subgroups that received lecture or Worked Example. Prior to the training they had a pre-test and another after the end of this phase. Results: Analysis of variance of repeated measures (ANOVA) was used in the statistical analysis. There was a significant difference between the grades before and after training (F1; 74 = 46,008; p <0.001) and between the course phases studied (F2; 148 = 19,452; p <0.001). There was no statistically significant difference between the groups (F2; 74 = 1.401; p = 0.240). There was no significant difference in mental effort reported in the comparison between groups (F1; 69 = 0.092; p = 0.762), but students in the 4th period had a significantly higher effort score. Variables extracted from verbal fluency tests do not explain student performance in the immediate posttest. Conclusions: Worked Example, which is a technique with good applicability for students, was equally effective as lecture, a well-known technique for teaching radiology.